PRAGMATISM IN IRAN’S FOREIGN POLICY AND RELATIONS WITH ARMENIA - Kal'bizade, El'nur Hasim (History, Archeology and Ethnography of the Caucasus, 2022)
The South Caucasus region has been one of the key directions of Iran’s foreign policy since 1991. Iran is closely interested in the processes that take place in the region, as it has historical ties, neighborly relations and common security interests. In the first years after the countries of the region regained their independence, analysts predicted that Iran would be able to establish closer ties with Azerbaijan in the South Caucasus. Such predictions were based on the fact that the Islamic Republic of Iran is a Muslim state and prefers an ideological approach to foreign policy. However, it soon became clear that Iran’s foreign policy is undergoing a transformation. There are elements of the transition from idealism to pragmatism in the country’s foreign policy. Contrary to expectations, Iran’s relations with Christian Armenia began to develop better than with Muslim Azerbaijan. The article examines the place of pragmatism in the foreign policy of Iran in the context of relations with Armenia. At the same time, it analyzes the effectiveness of the idealist approach in the foreign policy of Armenia, as a secular state. The article suggests that, although the conceptual foundations of Iran’s foreign policy are defined by the principles of idealism, they are pragmatic in their relations with Armenia. If we look at the Iran’s policy on the Caucasus since the 1990s, we can conclude that this policy was largely realistic and pragmatic, rather than ideological. In fact, the years when the Caucasus states, including Armenia, regained their independence coincided with Iran’s withdrawal from an ideological approach to foreign policy. At that time, Iran’s new regional foreign policy was based solely on national interests due to the ongoing geopolitical processes, and the expansion of the revolution was no longer a priority.
Keywords: pragmatism; idealism; ideological state; Iran; Armenia; South Caucasus; policy